GAMBARAN FAKTOR PREDIKTOR POSTOPERATIVE NAUSEA AND VOMITING (PONV) PASCA GENERAL ANESTESI DI RSUP DR TADJUDDIN CHALID MAKASSAR - M. Aidil; Made Suandika; Indri Heri Susanti; Etika Dewi Cahyaningrum (Sekolah Tinggi Pariwisata Mataram, 2022)
Nausea and vomiting are one of the side effects that often occur in patients with Postoperative Nausea and Vomiting (PONV). PONV can occur in 20-40% of surgical patients, the risk percentage increases in high-risk patients up to 80%. This study aims to determine the predictors of age, gender and BMI of PONV after general anesthesia at Dr Tadjudin Chalid Hospital Makassar. This research is a quantitative descriptive. The sample in this study were patients who experienced PONV after general anesthesia. The sampling technique used is accidental sampling with the Sloving formula so as to produce 65 respondents. As well as research instruments using instruments in the form of questionnaires and observation sheets (checklists). Data analysis used univariate analysis and bivariate analysis. The results obtained were based on age characteristics, 24 patients were found to have an age category of 25 – 39 years, namely there were 24 patients (36.9%). based on gender characteristics as many as 42 people or 64.6% and based on BMI characteristics 35 respondents (53.8%) had a body mass index in the normal range. Based on BMI characteristics, 35 respondents (53.8%) had a body mass index in the normal range.